CN102294212 (2011)
The invention relates to a glucose and temperature dual stimuli-responsive polymer hollow microcapsule, and a preparation method thereof. The polymer hollow microcapsule comprises: polymer with stimuli responsibility towards glucose, and polymer with stimuli responsibility towards temperature, wherein the mass ratio of the two is 1:5-2:1. The preparation method comprises steps that: a temperatureresponsive polymer shell layer with a cross-linked structure is formed on a silicon dioxide colloidal particle template; monomers with carboxylic acid groups are added; amino groups in aminophenylboronic acid are subject to a condensation reaction with the carboxylic acid groups; and silicon dioxide core is removed by using hydrofluoric acid, such that the product is obtained. According to the invention, the two stimuli-responsive components are relatively independent to each other, and the interference between the two is small. The preparation method is simple, and the method is suitable forindustrialized productions. The intelligent polymer hollow microcapsule has certain potential to be applied for carrying insulin, and for intelligently releasing insulin according to the variation ofglucose density in human blood. Therefore, the hollow microcapsule has potential application prospect in the field of diabetes mellitus treatment.